2008
DOI: 10.3174/ajnr.a1376
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Embolization of Cerebral Arteriovenous Malformations with Onyx

Abstract: BACKGROUND AND PURPOSE:Preoperative embolization facilitates the surgical management of complex cerebral arteriovenous malformations (cAVMs). This analysis aims to investigate the risks for preoperative cAVM embolization with Onyx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…The characteristics that make EVOH copolymer effective in the treatment of cerebrovascular lesions may benefit hemorrhagic lesions elsewhere in the body, and peripheral nonneurologic applications are becoming more accepted (2)(3)(4). Most of the literature on Onyx focuses on neurologic lesions (5,6) and chronic aortic endoleaks (7,8); the remaining literature on the topic largely comprises case reports and case series. In this study, we systematically reviewed the existing literature on the use of EVOH copolymer to treat acute hemorrhage outside of the head and neck to determine its efficacy and safety for use in peripheral lesions.…”
mentioning
confidence: 98%
“…The characteristics that make EVOH copolymer effective in the treatment of cerebrovascular lesions may benefit hemorrhagic lesions elsewhere in the body, and peripheral nonneurologic applications are becoming more accepted (2)(3)(4). Most of the literature on Onyx focuses on neurologic lesions (5,6) and chronic aortic endoleaks (7,8); the remaining literature on the topic largely comprises case reports and case series. In this study, we systematically reviewed the existing literature on the use of EVOH copolymer to treat acute hemorrhage outside of the head and neck to determine its efficacy and safety for use in peripheral lesions.…”
mentioning
confidence: 98%
“…[1][2][3][4][5][6] The aim of endovascular embolization is to achieve the occlusion of the nidus, preserving the venous outlet: the rationale is to devascularize the lesion, reducing the arterial blood flow into the nidus, and to maintain the patency of the venous drainage to avoid an increase in blood pressure in the AVM that could cause an intra-axial hemorrhage.…”
mentioning
confidence: 99%
“…Hauck et al 5 reported catheter entrapment in 4.9% of their AVM embolizations with Onyx. This has been addressed to some extent by the use of a new microcatheter with a detachable tip 6 ; however, this catheter is not available in the United States, and long-term associated outcomes are unknown.…”
Section: Discussionmentioning
confidence: 98%